LEGAL PROTECTION OF WORKERS WITH A SPECIFIC TIME WORK AGREEMENT (PKWT) IN THE TRANSFER OF OUTSOURCING COMPANIES FOLLOWING THE ENACTMENT OF LAW NO. 6/2023 - Liana, Liana; Yahman, Dr. Yahman (jfpublisher, 2024)
Employment relations can occur due to the existence of work, orders, and wages. Indonesian labor law recognizes two forms of employment relations, which are employment relations with a Specific Time Work Agreement (PKWT) and an Indefinite Time Work Agreement (PKWTT). This research aims to obtain further understanding of Government Regulation No. 6/2023 on Job Creation. This regulation is a result of the Government's efforts to fulfill legal protection of people's rights to work and a decent livelihood for humanity through job creation. This research uses a statutory approach and a conceptual approach. The types of legal materials used are primary, secondary and tertiary legal materials which are then systematically inventoried and categorized to solve real problems and try to formulate accurately, clearly and appropriately about the comparison of Law No. 13/2003 on Manpower and the Government Regulation on Job Creation (Law No. 6/2017 on the Stipulation of Government Regulation in Lieu of Law No. 2/2016 on Job Creation into Law). The results indicated that employees who are bound by a Specific Time Work Agreement (PKWT) after the enactment of the Government Regulation in Lieu of the Job Creation Law receive legal protection and compensation from outsourcing companies. This compensation is given to outsourced employees after the end of the work agreement, such as outsourcing companies, in accordance with the provisions stipulated in the preceding regulation.